Performance of Prototype of Optically Readout TPC with a 55Fe source. (April 2020) - Abritta Costa, I.; Baracchini, E.; Bellini, F.; Benussi, L.; Bianco, S.; Caponero, M.; Cavoto, G.; Di Marco, E.; Maccarrone, G.; Marafini, M.; Mazzitelli, G.; Messina, A.; et al.
Abstract: The performances of an optical readout of Time Projection Chambers (TPCs) with multiple Gas Electron Multipliers (GEMs) amplification stages are presented. The detector is characterized by using 55 Fe photons converting inside a 7 litre sensitive volume detector in different electric field configurations. This prototype is developed as part of the R&D for the CYGNO project for an application to direct Dark Matter search by detection of tracks of nuclear recoils in the gas within the keV energy range.